Future of Management of Multiple Sclerosis in the Middle East: A Consensus View from Specialists in Ten Countries. (17th December 2013) - Aljumah, Mohammed; Alroughani, Raed; Alsharoqi, I.; Bohlega, Saeed A.; Dahdaleh, Maurice; Deleu, Dirk; Esmat, Khaled; Khalifa, Ahmad; Sahraian, Mohammad A.; Szólics, Miklós; AlTahan, Abdulrahman; Yamout, Bassem I.; et al.
Abstract : The prevalence of multiple sclerosis (MS) is now considered to be medium-to-high in the Middle East and is rising, particularly among women. While the characteristics of the disease and the response of patients to disease-modifying therapies are generally comparable between the Middle East and other areas, significant barriers to achieving optimal care for MS exist in these developing nations. A group of physicians involved in the management of MS in ten Middle Eastern countries met to consider the future of MS care in the region, using a structured process to reach a consensus. Six key priorities were identified: early diagnosis and management of MS, the provision of multidisciplinary MS centres, patient engagement and better communication with stakeholders, regulatory body education and reimbursement, a commitment to research, and more therapy options with better benefit-to-risk ratios. The experts distilled these priorities into a single vision statement: "Optimization of patient-centred multidisciplinary strategies to improve the quality of life of people with MS." These core principles will contribute to the development of a broader consensus on the future of care for MS in the Middle East.